An exploratory examination of the viability and meaningfulness of time attitudes profiles in adults. (1st February 2017) - Cole, Jon C.; Andretta, James R.; McKay, Michael T.
Abstract: The temporal psychology literature has developed in recent years, both in terms of the volume of studies, and the sophistication of analyses. One area of particular interest is time attitudes, the way in which individuals feel about the past, present and future. Recently, results supporting the psychometric validity and internal consistency of Adolescent Time Inventory-Time Attitudes scores in adults have emerged. In the present study, person-centered analyses supported the viability of time attitudes profiles in an adult sample (N = 410), and showed that membership of those profiles related to a range of other temporal measures and symptoms of psychopathology. Five profiles emerged, two of which were associated with favorable outcomes such as a focus on the future alongside the lowest levels of depression (Positives and Optimists), two which were associated with unfavorable outcomes such as the highest levels of anxiety coupled with prominent fatalistic attitudes (Pessimists and Negatives), and a profile with outcomes falling between the poles (Ambivalents). It was noted that profiles were not related to alcohol-related problems. Highlights: Five time attitudes profiles emerged based on internally consistent scores. Positives and Optimists were future focused, and low on of depression. Pessimists and Negatives were fatalistic, reporting highest levels of anxiety. Ambivalents fell between these poles. Profiles were not related to alcohol-related problems.